Estudio de prefactibilidad para la instalación de una planta productora de agua saborizada enriquecida con vitaminas - Barriga Nalvarte, Yoel Miguel (2023)
This project consists of a pre-feasibility study for the facility of a plant to produce vitamin drinks. In this project, first, the plant macro-location analysis was carried out between the provinces of Lima, Cañete and Huaral; resulting chosen the province of Lima. Next, the microlocation analysis was carried out between the districts of Los Olivos, Ate and Lurin; being chosen Lurin. The calculated project demand amounts to 2 162 043 bottles in 500 ml presentation for the last of the 5 projected years. These bottles will be marketed in packs of 6 bottles (360 340 packs of 6 bottles). Regarding the technology of the project, the packaging process is the bottleneck as it has the lowest production capacity, 2 165 080 bottles of 500 ml per year. Regarding the economic and financial evaluation, an investment of approximately S/ 2 868 431 will be required; 40% of this amount will be financed by the investors/shareholders and 60% by banks through a loan. The financial analysis resulted in an economic VAN of S/ / 2 603 047, an TIR of 38.75% and COK gave a value of 15.21%. As for the social evaluation of our project, it can be clearly identified that it will benefit the population of Lurin directly through the generation of new jobs and indirectly by increasing the commercial dynamism in the area; there will be greater transit of people, etc. In addition, the company is committed to supporting the development of Lurin through social investment (implementation of schools, charitable institutions, etc.).